2021
DOI: 10.1186/s12883-021-02412-4
|View full text |Cite
|
Sign up to set email alerts
|

Hemogram parameters can predict in-hospital mortality of patients with Myasthenic crisis

Abstract: Background Myasthenia gravis (MG) is an autoimmune disease involving the neuromuscular junction. Myasthenic crisis (MC), which is characterized by respiratory failure and the requirement of mechanical ventilation in patients with MG, is still a medical emergency despite the decrease in mortality with the advances in acute management. Hemogram is a cost-effective test for evaluating hematological complications and systemic inflammation, and hemogram data have been used to predict various clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
(66 reference statements)
1
14
0
Order By: Relevance
“…Our study provides initial indications that routine laboratory parameters assessed before the onset of MC could be used as risk predictors for MC occurrence and facilitate early interventions (e.g., treatment with immunoglobulins or plasma exchange), possibly preventing MC and mitigate the associated morbidity and mortality. To this end, some studies have investigated prediction of in-hospital mortality in MC based on selected laboratory parameters (22, 35). A recent study derived a predictive score for in-hospital mortality of MC which used Myasthenia Gravis Foundation of America (MGFA) score at onset of the MC, septic shock, and cardiac arrest (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study provides initial indications that routine laboratory parameters assessed before the onset of MC could be used as risk predictors for MC occurrence and facilitate early interventions (e.g., treatment with immunoglobulins or plasma exchange), possibly preventing MC and mitigate the associated morbidity and mortality. To this end, some studies have investigated prediction of in-hospital mortality in MC based on selected laboratory parameters (22, 35). A recent study derived a predictive score for in-hospital mortality of MC which used Myasthenia Gravis Foundation of America (MGFA) score at onset of the MC, septic shock, and cardiac arrest (35).…”
Section: Discussionmentioning
confidence: 99%
“…The latter may corroborate our findings that increased leukocyte counts may be associated with increased risk for an ensuing MC. Further studies described a possible association between infections (36) and signs of inflammation (leukocytosis) (22) with an increased risk of developing MC. Furthermore, hemogram could provide clues to the course of the disease, as hematological changes have been identified as prognostic factors of mortality for several critical illnesses (22), e.g., endocarditis (37), acute kidney injury (38), and acute myocardial infarction (39, 40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors of mortality include age > 50 y, severe MG status, severe anemia, septic shock, cardiac arrest, number of comorbidities, ARDS and resuscitation need. 6,[12][13][14]91,92 In a retrospective study of 5000 hospital admissions for MG, there were no deaths observed in those <40 y of age, highlighting the importance of age and medical comorbidities as modifying factors for the mortality of MC. 14 Owing to better respiratory care and increased disease modifying treatment options, the prognosis of MC has improved strikingly over the last century.…”
Section: Prognosis Complications and Mortalitymentioning
confidence: 99%
“…Data on mortality worldwide range between 2 to 16%. Predictors of mortality include age > 50 y, severe MG status, severe anemia, septic shock, cardiac arrest, number of comorbidities, ARDS and resuscitation need 6,12–14,91,92 . In a retrospective study of 5000 hospital admissions for MG, there were no deaths observed in those <40 y of age, highlighting the importance of age and medical comorbidities as modifying factors for the mortality of MC 14 …”
Section: Prognosis Complications and Mortalitymentioning
confidence: 99%